Pengaruh Tingkat Kemiskinan dan Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia Indonesia - Heppi Syofya; Shintia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to explain the influence of poverty levels and economic growth on the human development index in Indonesia. This research is quantitative research using secondary data originating from the Central Statistics Agency (BPS) with panel data which is time series data for the 2019-2023 period and cross section data from 33 provinces in Indonesia. The data analysis method uses Descriptive Statistical Tests, uses the Classical Assumption Test, and also uses Hypothesis Testing. The conclusion from the results of this test is that the level of poverty and economic growth have an influence on the human development index.